Phase development and dielectric properties of (1-x)Pb(Zr0.52Ti0.48)O3-xBaTiO3ceramics - Wanwilai Chaisan (2018)
(1-x)Pb(Zr0.52Ti0.48)O3-xBaTiO3ceramics were prepared by a modified mixed-oxide method. The phase formation was studied by XRD analysis. All compositions exhibit complete solid solutions of perovskite-like phase in the (1-x)PZT-xBT system. The (2 0 0)/(0 0 2) peak was found to split at the composition x = 0.6 and the co-existence of tetragonal-rhombohedral phases occurs with x ≤ 0.6. The possible range of compositions which correspond to a phase transition is 0.6 < x < 0.7. While pure BT ceramics exhibited a sharp phase transformation expected for normal ferroelectrics, phase transformation behavior of the (1-x)PZT-xBT solid solutions became more diffuse with increasing BT contents. This was primarily evidenced by an increased broadness in the dielectric peak, with a maximum peak width occurring at x = 0.5. © 2006 Elsevier B.V. All rights reserved.